Produccion de toxina por el Clostridium hemolyticum I.- Tiempo optimo de su produccion - Gonzalez, M.=700 1 Pedroso, M.; Perez, H.
(En, Es)
Ilus., 12 ref.
Keywords: TOXINAS; CLOSTRIDIUM; TIEMPO; PRODUCCION; CUBA; REVISTA DE SALUD ANIMAL